Profiling in basketball: Physical and physiological characteristics of elite players - Ostojic, S. M.; Mazic, S.; Dikic, N. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to describe structural and functional characteristics of elite Serbian basketball players and to evaluate whether players in different positional roles have different physical and physiological profiles. Five men's basketball teams participated in the study and competed in the professional First National League. Physiological measurements were taken of 60 players during the final week of their preparatory training for competition. According to positional roles, players were categorized as guards (n = 20), forwards (n = 20), and centers (n = 20). Guards were older (p < 0.01) and more experienced (p < 0.01) as compared with both forwards and centers. Centers were taller and heavier than guards and forwards (p < 0.01), whereas forwards had significantly higher height and weight than guards (p < 0.01). Centers had more body fat (p < 0.01) as compared with forwards and guards. Also, centers had significantly lower estimated [latin capital V with dot above]O2max values (p < 0.01) compared with forwards and guards. In addition, the highest heart rate frequencies during the last minute of the shuttle run test were lower in guards (p < 0.01) as compared with forwards and centers. Vertical jump power was significantly higher in centers (p < 0.01) as compared with guards. The results of the present study demonstrate that a strong relationship exists between body composition, aerobic fitness, anaerobic power, and positional roles in elite basketball.